Biochemical and Nutritional Changes during Food Processing and Storage - Orlien, Vibeke; Bolumar, Research Scientist (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Food processing by humans goes a long way back in time, e.g., heat for cooking was used 1.9 million years ago. However, meal preparation now seems to be moving out of the home kitchen, and preprocessed or processed/convenience food products are becoming a larger part of the daily diet. In addition, consumers are progressively focusing on the impact of food on their health, and they demand foods that have a high nutritional quality and an aroma and natural flavor that are similar to freshly-made products. Therefore, nutritional quality is concurrent with food safety, and sensory perception is becoming an increasingly important factor in food choices. The human digestive tract disintegrates food to allow the nutrients to be released and made available to the body. However, nutrients can undergo unwanted degradation upon processing and subsequent storage, negatively influencing the physiological effects. Different processing techniques will result in different food structures, thereby also affecting bioaccessibility and nutritional value. Hence, food scientists and industry have an increased interest in both conventional and innovative processing methods that can provide good-quality products with high nutritional value and stable shelf life. This Special Issue aims to shed some light on the latest knowledge about and developments within the effects of food processing and storage on changes of biochemical and nutritional compounds. Both original research articles and reviews are included in this book.